Perancangan Video 3D mengenai Senjata Tradisional dari Asia Timur - Anggrianto, Vicky; Pratama, Jimmy (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
A three-dimensional object is an object that has the attributes length, width and height. With the fast improvement of technology, there are various ways to distribute information. One of the way is to create an 3D based animation video. 3D object video is a video that shows an 3D model with huge amount of detail to look as close to reality as possible from different angle. The objective of this research is to design a video animation based on 3D object to spread information about the traditional weapon of East Asia. This research uses qualitative method by interview to 30 university students as respondent. Multimedia Development Life Cycle is used as the method to produce the video. Based on the answer that was collected from the interview we can come to an agreement that with the assistance of 3D animation, information can be easier to understand because of the 3D object. The result of this research is a 3D animation video about the traditional weapon of East Asia.